Сто великих научных открытий: научно-популярная литература / Д. К. Самин - Самин Д. К. (100 великих, 2002)
Экземпляры: (20161028) / Инвентарный номер: 2058 / Цена: / Сис.шифр: 72.3 / Авт.знак: С17 / ГРНТИ: 03.09 / ББК: 72.3